SPEAK THE STUDENT'S LANGUAGE TO COMPLETE THE CONTEXTUAL LISTENING ASSESSMENT - Marhaeni K.D Matondang; Tutiariani Nasution; Tiodora Fermiska Silalahi; Rosmeri Saragih (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2023)
The research aims to describe the form of student speech acts, especially students' questioning speech acts in contextual listening activities. Contextual listening is related to listening activities and what is happening in everyday life. This research method uses the pattern used is grounded research pattern, that is, researchers are prioritized to be able to develop knowledge and several theories after knowing the problems and field data. In this case, the researcher enters a social situation by collecting data, in this way the researcher takes the data source using a purposive sampling technique, namely a technique for taking data sources with certain considerations, in the case that the researcher takes into consideration 2 English literature students. The results of the research are that it is known that students will have their patterns in the speech act of asking questions. It is known that student A uses questions more often by using speech acts in the form of directives 9 times followed by 1 time commissive, 1 time expressive, or 1 time representative, by focusing on the student appointed to answer the question, while Student 2 uses more commissive speech acts 4 times and uses representative 2 times, this shows that many of the questions given by the teacher are more challenging for students to answer and not burdensome for one student, but for students who are ready to answer questions. Thus, it can be concluded that contextual listening activities allow students to carry out speaking activities through active speech. In this case, it is also emphasized that when students listen well, it will give them the ability to ask questions to understand the material being taught.